Α-Fe2O3/TiO2 3D hierarchical nanostructures for enhanced photoelectrochemical water splitting. Issue 1 (22nd November 2016) - Han, Hyungkyu; Riboni, Francesca; Karlicky, Frantisek; Kment, Stepan; Goswami, Anandarup; Sudhagar, Pitchaimuthu; Yoo, Jeongeun; Wang, Lei; Tomanec, Ondrej; Petr, Martin; Haderka, Ondrej; Terashima, Chiaki; et al.
Abstract : α-Fe2 O3 /TiO2 3D-hierarchical nanostructures with enhanced PEC properties compared to pure TiO2 due to improved separation of photogenerated charge carriers. Abstract : We report the fabrication of 3D hierarchical hetero-nanostructures composed of thin α-Fe2 O3 nanoflakes branched on TiO2 nanotubes. The novel α-Fe2 O3 /TiO2 hierarchical nanostructures, synthesized on FTO through a multi-step hydrothermal process, exhibit enhanced performances in photo-electrochemical water splitting and in the photocatalytic degradation of an organic dye, with respect to pure TiO2 nanotubes. An enhanced separation of photogenerated charge carriers is here proposed as the main factor for the observed photo-activities: electrons photogenerated in TiO2 are efficiently collected at FTO, while holes are transferred to the α-Fe2 O3 nanobranches that serve as charge mediators to the electrolyte. The morphology of α-Fe2 O3 that varies from ultrathin nanoflakes to nanorod/nanofiber structures depending on the Fe precursor concentration was shown to have a significant impact on the photo-induced activity of the α-Fe2 O3 /TiO2 composites. In particular, it is shown that for an optimized photo-electrochemical structure, a combination of critical factors should be achieved such as (i) TiO2 light absorption and photo-activation vs. α-Fe2 O3 -induced shadowing effect and (ii) the availability of free TiO2 surface vs. α-Fe2 O3 -coated surface. Finally, theoretical analysis, based on DFT calculations, confirmed the optical properties experimentally determined for the α-Fe2 O3 /TiO2 hierarchical nanostructures. We anticipate that this new multi-step hydrothermal process can be a blueprint for the design and development of other hierarchical heterogeneous metal oxide electrodes suitable for photo-electrochemical applications.